Perlindungan Hukum Anak Nakal dalam Penjatuhan Sanksi Pidana - I Made Dharma Putra; I Nyoman Putu Budiartha; A. Sagung Laksmi Dewi (Jurnal Preferensi Hukum, 2020)
Children are an inseparable part of human survival and the survival of the nation and state. Today delinquency and crimes committed by children continues to increase, such as narcotics abuse, robbery, theft and rape, destruction of property and so on. When delinquency committed by children even leads to criminal acts, of course this is very disturbing for the community. The existence of legal protection for naughty children in criminal sanctions is of course very desirable for the best interests of children who are in conflict with the law. The method used in this research is normative legal research or what is also called the term library research by examining document studies using secondary data, namely laws, legal theory, expert opinion and so on. The result of this research is that the process of examining criminal cases against delinquents and starting investigations, arrests, detention, prosecution, trials and placement at the correctional center must pay attention to children's rights, as well as legal protection of delinquents in imposing criminal sanctions where child protection aims to provide guarantees for children in conflict with the law. In this case, special investigators for children, investigations with a family atmosphere, investigators do not use service attributes, duties to carry out diversity, child secrecy and arrest must of course put Restorative Justice, and the fall of criminal sanctions against children must be based on truth, justice and child welfare. So that Law Enforcement Apparatus both the Police as Investigators, Public Prosecutors, and Child Judges with the enactment of Law Number 11 of 2012 concerning the Juvenile Justice System.